Bone metastases and immunotherapy in patients with advanced non-small-cell lung cancer. Issue 1 (21st November 2019) - Landi, Lorenza; D'Incà, Federica; Gelibter, Alain; Chiari, Rita; Grossi, Francesco; Delmonte, Angelo; Passaro, Antonio; Signorelli, Diego; Gelsomino, Francesco; Galetta, Domenico; Giannarelli, Diana; Soto Parra, Hector; et al.
Abstract : Background: Bone metastases (BoM) are a negative prognostic factor in non-small-cell lung cancer (NSCLC). Beyond its supportive role, bone is a hematopoietic organ actively regulating immune system. We hypothesized that BoM may influence sensitivity to immunotherapy. Methods: Pretreated non-squamous (cohort A) and squamous (cohort B) NSCLCs included in the Italian Expanded Access Program were evaluated for nivolumab efficacy according to BoM. Results: Cohort A accounted for 1588 patients with non-squamous NSCLC, including 626 (39%) with (BoM+) and 962 (61%) without BoM (BoM-). Cohort B accounted for 371 patients with squamous histology including 120 BoM+ (32%) and 251 (68%) BoM- cases. BoM+ had lower overall response rate (ORR; Cohort A: 12% versus 23%, p < 0.0001; Cohort B: 13% versus 22%, p = 0.04), shorter progression free survival (PFS; Cohort A: 3.0 versus 4.0 months, p < 0.0001; Cohort B: 2.7 versus 5.2 months, p < 0.0001) and overall survival (OS; Cohort A: 7.4 versus 15.3 months, p < 0.0001; Cohort B: 5.0 versus 10.9 months, p < 0.0001). Moreover, BoM negatively affected outcome irrespective of performance status (PS; OS in both cohorts: p < 0.0001) and liver metastases (OS cohort A: p < 0.0001; OS Cohort B: p = 0.48). At multivariate analysis, BoM independently associated with higher risk of death (cohort A: HR 1.50; cohort B: HR 1.78). Conclusions: BoM impairs immunotherapy efficacy. Accurate bone staging should be included in clinical trials with immunotherapy.